Gerstmann-Straussler-Scheinker disease: novel PRNP mutation and VGKC-complex antibodies. - Jones, M; Odunsi, S; du Plessis, D; Vincent, A; Bishop, M; Head, M; Ironside, J; Gow, D (Lippincott Williams and Wilkins, 2014)
OBJECTIVE: To describe a unique case of Gerstmann-Straüssler-Scheinker (GSS) disease caused by a novel prion protein (PRNP) gene mutation and associated with strongly positive voltage-gated potassium channel (VGKC)-complex antibodies (Abs). METHODS: Clinical data were gathered from retrospective review of the case notes. Postmortem neuropathologic examination was performed, and DNA was extracted from frozen brain tissue for full sequence analysis of the PRNP gene. RESULTS: The patient was diagnosed in life with VGKC-complex Ab-associated encephalitis based on strongly positive VGKC-complex Ab titers but no detectable LGI1 or CASPR2 Abs. He died despite 1 year of aggressive immunosuppressive treatment. The neuropathologic diagnosis was GSS disease, and a novel mutation, P84S, in the PRNP gene was found. CONCLUSION: VGKC-complex Abs are described in an increasingly broad range of clinical syndromes, including progressive encephalopathies, and may be amenable to treatment with immunosuppression. However, the failure to respond to aggressive immunotherapy warns against VGKC-complex Abs being pathogenic, and their presence does not preclude the possibility of prion disease.